Territorial Planning and Sustainable Development: A Case Study from the APA São Francisco Xavier-SP - Henrique,Raquel (2021)
Abstract This article is a case study from the APA São Francisco Xavier, located in the municipality of São José dos Campos-SP, and aims to evaluate the effectiveness of this UC category as an instrument of territorial planning to fulfill its role of reconciling conservation and socio-economic development, based on the sustainable use of natural resources. This study applied multi-methods - both qualitative and quantitative approaches - using fieldwork, participant observation, questionnaires, and geoprocessing to collect and analyze both primary and secondary data. The results demonstrate that APA promotes conservation, but is not free from threats and does not have effective and permanent means to guarantee the promotion of socio-economic development based on the sustainable use of its natural resources. The study suggests that territorial planning should be articulated between the levels of government, its different agencies, and the local community.